Scientific concepts and basic principles of transmedia projects (concepts of Robert Pratten and Jeff Gomez) (Herald of Journalism, 2019)
The study of different media, the study of their nature and features in the digital era is of great importance for understanding the trends in the functioning of the media and forecasting future de-velopment. Determining the benefits and negative consequences of information technology for society and people, identifying the causes of media processes occurring in today’s world are becoming impor-tant issues on the agenda.The purpose of this article is to identify ways to solve the key problems of the domestic media space by analyzing the scientific concepts and basic principles of transmedia. Analysis of the role of transmedia in the development of domestic information technologies and new media. The scientific and practical value of the study is to determine the importance of transmedia strategies in the digital age, the study of its conceptual foundations. To ensure the accuracy of scientific forecasting, it is important to consider the influence of advanced information technologies on the communications system.The value of the article. The article analyzes and systematizes the scientific concepts of interna-tionally recognized experts in transmedia technologies and transmedia storytelling. Recommendations for analyzing interrelated processes in the field of information and communication technologies are proposed. The author used effective scientific methods necessary for identifying and predicting political and communicative processes. The article is written with the aim of promoting research on the development of society, the preservation of national identity in the era of information and technological transformation.
Keywords: transmedia, scientific concepts and principles, transmedia strategies, trends in digital media, transmedia storytelling.